MATHEMATICAL MODEL BETWEEN BASELINE AND MINIMUM VISA TIME WITH HIGH-PRECISION GNSS TECHNOLOGY. - MENDOZA DUEÑAS, JORGE LUIS; TORRES ALAYO, MARIO MARTIN (Journal of Namibian Studies)
In relation to the observation of baselines with high precision GNSS receivers, there are few studies where the minimum observation time of a baseline is established with respect to its length, in certain guides of recognized GNSS receiver brands certain observation times are recommended depending on the baseline length, But it is not supported why, nor how such a recommendation is reached. The Peruvian technical standard only establishes a minimum observation time regardless of the length of the baseline. In terms of productivity and efficiency, establishing a relationship between the minimum observation time for a given baseline length is reasonable. In the present study, the relationship between the minimum visa time (observation) required for a given baseline length is found, through a mathematical relationship. For this purpose, different baselines were observed at different time intervals, then these sets of measurements were subjected to statistical methods to eliminate observation errors. With these results the minimum observation time is related to its baseline length, obtaining a linear relationship, these results are similar to the recommendations in the geodetic receiver guides. Therefore, the results in the present study are satisfactory and coherent and also suggestive to the realization of further studies using other brands of receptors, suggesting observations at larger and different lengths of baselines.